A VIOLÊNCIA CONTRA MULHER COMO FATOR DE RISCO PARA O DESENVOLVIMENTO DO TRANSTORNO DE ESTRESSE PÓS-TRAUMÁTICO - Souza, Celia Mendes de (2017)
This study aimed to investigate violence against women as a risk factor for the development of Post Traumatic Stress Disorder (PTSD) and its associations with the psychodynamics of these subjects. The participants were five women, aged over 18 years, victims of violence and attended at a Reference and Support Center for Women in the metropolitan region of São Paulo. At first, a questionnaire was used to collect sociodemographic data, past history of the subject and crime (violence suffered). The other instruments used were: the Childhood Trauma Questionnaire (QUESI), the Traumatic Stress Symptom Screening Instrument (Portuguese version of the Screen for Posttraumatic Stress Symptoms - SPTSS) And the Thematic Apperception Test. For the development of the present study the qualitative descriptive combined with a quantitative analysis was carried out as a research method, based on the data obtained in the questionnaire and the scale. The results indicate that four of the five participants present symptoms compatible with the disorder, confirming the hypothesis that the violence committed against women contributes to the development of symptoms related to Post Traumatic Stress Disorder, evidencing itself as one of the risk factors For the occurrence of the disorder. The experience of the situation of violence in a chronic and / or prolonged way appears as aggravating in the appearance and maintenance of the symptoms; On the other hand, social support, favorable family history and perception of aggression as violence and crime are considered as protective factors in this condition.